Analisis Perbandingan Efek Arus Modal Investor Domestik dan Asing terhadap Perubahan IHSG - Krisna Darmawan; Vitriyani Tri Purwaningsih; Muhammad Mufti Hudani (Diponegoro Journal of Economics, 2025)
This study aims to analyze and compare the impact of capital flows from domestic investors and foreign investors on changes in the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange. Capital flows are analyzed based on eight transaction categories classified according to the type of participant (foreign and domestic investors) and the type of transaction (value and volume). The method used is multiple linear regression with time series data of 476 observations from 2023 to 2024 sourced from the Indonesia Stock Exchange. The results indicate that transactions by domestic investors from foreign investors, show negative coefficients, implying a downward pressure on the IHSG. This study compares the effects of both domestic and foreign investors, providing an examination from the perspective of transaction types. The originality of this research lies in its disaggregated and direct comparison of domestic and foreign investor transactions within a unified empirical framework, whereas most existing studies focus primarily on foreign flows alone.